THE RELATIONSHIP BETWEEN LONG WAITING TIME ON PATIENT SATISFACTION OUT PAGE IN INSTALLATION POLYCLINIC OUTCOMING AT NADHLATUL ULAMA TUBAN HOSPITAL - Surotul Ilmiah; Adibah Enggar; Ah Yusuf (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Patient satisfaction is the level of one's feelings after comparing the perceived performance with expectations, so the level of satisfaction is a function of the difference between perceived performance and expectations. Patients are people who consult health issues to obtain the necessary health services, both directly and indirectly to the doctor. Satisfaction can be interpreted if it is in line with expectations and reality, service during the process of enjoying services, employee behavior, physical atmosphere and physical conditions, and promotion is not in accordance with reality. This study uses an observational analytic design with a cross sectional approach. The research sample of 60 internal medicine polyclinic patients at Nahdlatul Ulama Hospital Tuban was selected by accidental sampling. research instruments, patient satisfaction questionnaire. The results showed that there was a relationship between Waiting Time and Patient Satisfaction in the Internal Medicine Polyclinic in Outpatient Installation, this was evidenced by the Spearman Rho test obtained p = 0.00 (α <0.05). It is expected that the results of this study can be used as information for the hospital management, that waiting time is also included that affects satisfaction.